A Contemporary Review of High Voltage Partial Discharge Detection and Recognition Techniques - Zul Hasrizal Bohari,; Isa, Muzamir; Abu Bakar, Faizah; Abdullah, Ahmad Zaidi; Nanyan, Ayob Nazmy; Mohamad Na’im Mohd Nasir,; Mohamad Fani Sulaima,; Emy Zairah Ahmad, (Journal of Advanced Research in Fluid Mechanics and Thermal Sciences, 2023)
This review article provides a summary of the most advanced approaches and advancements in the detection and recognition of high voltage partial discharge (PD). It discusses numerous detecting technologies, such as electrical, acoustic, and optical approaches, as well as their merits and disadvantages. It also discusses current developments in signal processing and pattern recognition algorithms used for PD detection and classification. Lastly, the study covers the challenges and limitations in high voltage PD detection and identification studies, as well as potential future solutions.